碑铭与外语档案研究 庄钦永博士专访: An Interview with Dr. David Chng Khin Yong Research Studies on Inscriptions and Foreign Language Archives - Sing Ee, Ooi (ERUDITE: Journal of Chinese Studies and Education, 2024)
近年来，利用碑刻资料如神主牌、碑记及墓碑文字已成为星马学术界普遍的治学方法，外语档案则依然较少为学者使用。阅读外语档案考验一名学者坐冷板凳的毅力，并非简单的差事。尽管庄钦永使用外语档案开拓星马华人史研究的新路径，写下不少具有新见的学术成绩，然这份耗尽时间、心力与经费的工作，似乎难以吸引年轻学人追随。专访缘起于笔者在撰写博士论文期间，向庄钦永先生请教伦敦布道会与美部会传教士档案。相较于星马两地学者在情感上对传教士及其研究排斥，在方法上依旧围绕在已被使用殆尽的中文史料撰写华人史议题；庄钦永利用外语档案开拓新加坡华人史、教育史、甲必丹等研究的新路径，让人耳目一新。《新加坡华人史论丛》等著作是庄钦永早期利用碑记资料与外语档案等材料考证的成果；后期则专注于传教士研究，跨足在基督教史、汉语新词和翻译史。采访详述庄钦永在澳洲国立大学利用科技作为历史研究工具、在新甲剔藓寻碑的艰辛历程及多次到国外查阅档案的经验，其所展现丰硕的成果，冀可鼓舞年轻学人善用原始档案在各自领域有所拓展。In recent years, inscribed materials have become commonly used in the academic fields of Singapore and Malaysia, while foreign language archives remain less utilized by scholars. Even though Dr. Chng has pioneered new paths in the study of the Chinese history of Singapore and Malaysia by using foreign archives and has produced many groundbreaking academic achievements, this approach struggles to attract younger scholars due to the time and financial investment required. My interview with Dr. Chng stemmed from my doctoral research, seeking his expertise on the London Missionary Society and American Board of Commissioners for Foreign Missions archives. Unlike scholars who predominantly rely on exhausted Chinese historical materials, Dr. Chng's use of foreign archives has opened new paths in the Chinese history of Singapore, educational history, and Kapitan studies. His works as “Collected Essays on Chinese in Nineteenth Century Singapore” reflect his early successes in archival research. Later, he delved into missionary studies, Christianity history, new Chinese words, and translation history. The interview highlights Dr. Chng's academic journey, starting from his use of technology for historical research at the Australian National University, to the arduous process of searching for inscriptions in cemeteries and repeated visits to foreign countries for archival research. These fruitful experiences are intended to inspire young scholars to effectively utilize primary sources to expand their respective fields.Keywords: Inscriptions, foreign language archives, Chinese history of Singapore and Malacca, missionary studies, history of translation